Groundwater quality and its suitability for drinking and irrigational purpose in Bhojpur district: middle Gangetic plain of Bihar, India - Subodh Kumar; Anand Kumar; Prashant; V. N. Jha; Sunil Kumar Sahoo; Rajesh Kumar Ranjan (Water Supply, 2022)
A total of 138, samples have been collected in both pre and post monsoon season to understand the seasonal variability in groundwater quality and its suitability for drinking and domestic water supply. The samples were analysed for physical parameters, major ions along with fluoride and uranium. The results were integrated with GIS to represent both seasonal and spatial variations of groundwater quality parameters, drinking groundwater quality index (DGQI) and irrigation groundwater quality index (IGQI). Results show that groundwater is alkaline in nature and largely controlled by the silicate weathering, ion exchange and reverse ion exchange processes. However high nitrate concentration exceeding the WHO guideline suggests the influence of anthropogenic activities on groundwater quality. The average values of the major ions concentrations was found higher in pre monsoon season due to change in the recharge. The DGQI values of 6 samples in pre monsoon and 2 samples in post monsoon season falls under poor water quality. However, individual irrigation indices along with the combine IGQI indicate groundwater is suitable for irrigation in both the seasons. These results along with the seasonal and spatial variability map may help the decision makers in planning for better domestic and irrigation water supply. HIGHLIGHTS Silicate weathering and ion exchange controls ionic species in groundwater.; High concentration of nitrate in pre-monsoon season suggests influence of anthropogenic activities on groundwater.; Relatively high ion concentrations are found in pre-monsoon season.; Groundwater is safe in terms of fluoride and uranium.; Both DGQI and IGQI suggests that groundwater is safe for drinking and domestic water supply.;